(untitled) (SAARC Journal of Agriculture, 2018)
The present study was undertaken to evaluate the effect of different levels of wheat flour on the quality characteristics of chicken meatball. Wheat flour which acts as a binding agent of meatball except for control group T1. The meatballs were formulated having 0%, 5%, 10% and 15% wheat flour. The sensory (colour, flavour, texture, juiciness, tenderness, overall acceptability), physicochemical (proximate analysis, pH, cooking loss), biochemical (TBARs, POV, FFA) were analyzed. Treatments were analyzed in a 4×3 factorial experiment in CRD replicated three times per cell. Wheat flour inclusion in meatballs increased cooking yield by reducing weight loss from 27.06 to 26.49%. Among four treatments most preferable colour, odour, tenderness, juiciness was observed significantly (p<0.05) at 15% wheat flour group and the less preferable colour was observed from the control group. The preferablecolourwas observed at 0 days and less preferable colour at 30 day. Meatballs made with the addition of 15% wheat flour had the highest tenderness, overall acceptability, raw pH, cooked pH and lower DM, ash, PV and TBA & showed significant value (p<0.05) The cooked pH was decreased with the increased storage period. Meatballs with wheat flour inclusions at 15% were most acceptable. It is recommended that further studies of the wheat flour inclusion in meatballs production be carried out to ensure the availability of cheaper, nutritious and acceptable convenience food in the Bangladeshi market. SAARC J. Agri., 16(1): 205-213 (2018)